The Convergence of High-Consequence Livestock and Human Pathogen Research and Development: A Paradox of Zoonotic Disease - Michelotti, Julia M.; Yeh, Kenneth B.; Beckham, Tammy R.; Colby, Michelle M.; Dasgupta, Debanjana; Zuelke, Kurt A.; Olinger, Gene G. (My University, 2018)
The World Health Organization (WHO) estimates that zoonotic diseases transmitted from animals to humans account for 75 percent of new and emerging infectious diseases. Globally, high-consequence pathogens that impact livestock and have the potential for human transmission create research paradoxes and operational challenges for the high-containment laboratories that conduct work with them. These specialized facilities are required for conducting all phases of research on high-consequence pathogens (basic, applied, and translational) with an emphasis on both the generation of fundamental knowledge and product development. To achieve this research mission, a highly-trained workforce is required and flexible operational methods are needed. In addition, working with certain pathogens requires compliance with regulations such as the Centers for Disease Control (CDC) and the U.S. Department of Agriculture (USDA) Select Agent regulations, which adds to the operational burden. The vast experience from the existing studies at Plum Island Animal Disease Center, other U.S. laboratories, and those in Europe and Australia with biosafety level 4 (BSL-4) facilities designed for large animals, clearly demonstrates the valuable contribution this capability brings to the efforts to detect, prepare, prevent and respond to livestock and potential zoonotic threats. To raise awareness of these challenges, which include biosafety and biosecurity issues, we held a workshop at the 2018 American Society for Microbiology (ASM) Biothreats conference to further discuss the topic with invited experts and audience participants. The workshop covered the subjects of research funding and metrics, economic sustainment of drug and vaccine development pipelines, workforce turnover, and the challenges of maintaining operational readiness of high containment laboratories.
Citation: Michelotti, J.M.; Yeh, K.B.; Beckham, T.R.; Colby, M.M.; Dasgupta, D.; Zuelke, K.A.; Olinger, G.G. The Convergence of High-Consequence Livestock and Human Pathogen Research and Development: A Paradox of Zoonotic Disease. Trop. Med. Infect. Dis. 2018, 3, 55.
Keywords: Biosafety; Biosecurity; Bsl-3-Ag; High-Consequence Pathogen Research; Zoonotic Disease